Does forest disturbance matter to climate degradation? Evidence from top Asian Economies - Haseeb, Muhammad; Staniewski, Marcin; Mihardjo, Leonardus Wahyu Wasono; Awruk, Katarzyna (Technological and Economic Development of Economy, 2021)
The main purpose of this study was to examine the relationship between forestry and climate degradation in the modern era. Specifically, the study aimed to examine how forest areas are influencing environmental degradation. Given the inevitable link between forests and carbon dioxide (CO2), the current study focused on examining the impact of changes in forestry on the levels of CO2 emissions in top Asian economies, including China, India, Indonesia, Malaysia, and Thailand. To this end, the current study was quantitative in nature and utilized advanced methodology such as econometrics of quantile-on-quantile (Q-Q) regression to investigate the forests-environmental degradation link. In particular, we examined the effect of quantiles of forest areas on the quantile of climate change in top Asian economies using the time series data from 1990 to 2018. The findings confirmed that forest areas have a negative and significant impact on climate degradation in the majority of the groups of quantiles for all countries. Therefore, this study highlights the importance of forests in controlling environmental degradation in Asian economies. Lastly, the study recommends the respective government bodies to intervene and provide assistance in environmental initiatives to improve forestry levels. First published online 09 February 2021